Detection and isolation of flavonoids from Calendula officinalis (F.Asteraceae) cultivated in Iraq - N. Hamad, Maha (Iraqi Journal of Pharmaceutical Sciences, 2017)
Calendula officinalis L. (Asteraceae) known as marigold is known to have several pharmacological activities and used for the treatment of several diseases as measles, jaundice, constipation and several inflammations. Marigold flowers contain several chemical constituents mainly flavonoids, triterpenoids and essential oil. In this study marigold flowers cultivated in Iraq had been investigated for its flavonoids content. The study revealed the presence of quercetin and kaempferol glycosides and the absence of myricetin glycosides. The flowers were extracted with ethanol 70% fractionated with different solvent and the flavonoids were isolated by preparative HPLC. The isolated flavonoids were identified by measuring melting points, UV, IR, analytical HPLC and TLC.Keywords: Marigold, Flavonoids, Kaempferol, Preparative HPLC.